A robust lyophilized kit for convenient one-step formulation of [68Ga]Ga-DOTA-E−[c(RGDfK)]2 in hospital radiopharmacy for clinical PET imaging. (June 2023) - Das, Soumen; Sahu, Sudeep; Chakraborty, Avik; Kamaleshwaran, K.K.; Bannore, Trupti Upadhye; Damle, Archana; Chakravarty, Rubel; Chakraborty, Sudipta
Abstract: The present article describes the development of robust lyophilized kit for convenient formulation of [ 68 Ga]Ga-DOTA-E−[c(RGDfK)]2 (E = glutamic acid, R = arginine, G = glycine, D = aspartic acid, f = phenylalanine, K = lysine) radiopharmaceutical for clinical use in non-invasive monitoring of malignancies overexpressing integrin αv β3 receptors. Five batches of the kit were prepared with optimized kit contents, all of which showed high 68 Ga-radiolabeling yield (>98%). Pre-clinical evaluation of the [ 68 Ga]Ga-radiotracer in SCID mice bearing FTC133 tumour exhibited significant accumulation in the tumor xenograft. Preliminary human clinical investigation carried out in a 60 year old male patient with metastatic lung cancer revealed high radiotracer uptake in the tumor along with satisfactory target to non-target contrast. The developed kit formulation also showed a long shelf-life of at least 12 months on storage at 0 °C. All these results point towards the promising attributes of the developed kit formulation for convenient preparation of [ 68 Ga]Ga-DOTA-E−[c(RGDfK)]2 for routine clinical use. Highlights: A lyophilized kit of DOTA-E−[c(RGDfK)]2 developed. It enabled convenient formulation of [ 68 Ga]Ga-DOTA-E−[c(RGDfK)]2 for routine clinical use. Pre-clinical PET-CT imaging showed significant accumulation of the radiotracer in tumor. Preliminary human clinical investigations showed good uptake of the radiotracer in cancer lesions and satisfactory image contrast.